The influence of desilication/dealumination processes on the physicochemical properties of clinoptilolite. (22nd April 2019) - Wojciechowska, Kamila
Abstract: A clinoptilolite was exposed to treatments with acid and base solutions that caused desilication, dealumination or a combination of both. The mineralogical and physicochemical properties of clinoptilolite were studied by X-ray diffraction, X-ray fluorescence, Brunauer–Emmett–Teller specific surface area, differential thermogravimetry, Fourier-transform infrared spectroscopy and scanning electron microscopy methods. The studies provided insight into the structural and textural properties of the treated zeolite. The applied post-synthesis modification techniques proved to be effective for the generation of secondary mesopores.